2010
DOI: 10.1111/j.2042-3306.2010.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance parameters and post exercise heart rate recovery in Warmblood sports horses of different performance levels

Abstract: SummaryReasons for performing study: Standardised exercise tests are used for fitness evaluation of sports horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 21 publications
2
34
1
Order By: Relevance
“…In contrast, for the cross-country phase we found that heart rates had decreased by about 53% of HR peak values 180 seconds after the completion of the course and that the mean regression line was characterised by high correlation (r2= 0.92). Similar findings were obtained by Bitschnau et al (2010) in warmblood horses during a treadmill test, in which a post exercise decrease in heart rate to 50% of the maximal HR in the first 3 minutes was recorded. Thus, HRR is an appropriate parameter for evaluating workload after high-intensity, but not low-intensity, exercise and may represent a useful marker of fitness level, ability and soundness; however, the usefulness of this parameter should not be overestimated for the evaluation of workload following low-intensity exercise, when HR recovery may be influenced by other factors.…”
Section: Competition Phasessupporting
confidence: 67%
“…In contrast, for the cross-country phase we found that heart rates had decreased by about 53% of HR peak values 180 seconds after the completion of the course and that the mean regression line was characterised by high correlation (r2= 0.92). Similar findings were obtained by Bitschnau et al (2010) in warmblood horses during a treadmill test, in which a post exercise decrease in heart rate to 50% of the maximal HR in the first 3 minutes was recorded. Thus, HRR is an appropriate parameter for evaluating workload after high-intensity, but not low-intensity, exercise and may represent a useful marker of fitness level, ability and soundness; however, the usefulness of this parameter should not be overestimated for the evaluation of workload following low-intensity exercise, when HR recovery may be influenced by other factors.…”
Section: Competition Phasessupporting
confidence: 67%
“…Previous studies highlighted either HR (Von Borell et al, 2007;Bitschnau et al, 2010) or eye temperature (Hall et al, 2011;McGreevy et al, 2012;Valera et al, 2012) as good indicators of stress in horses. Specifically, IRT has been used to assess acute stress in the elk during velvet antler removal (Cook et al, 2006) and in calves during disbudding (Stewart et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, event horses and ponies were, according to the above protocol, divided into average or good performers (AP or GP, respectively) depending on whether the individual V LA4 and HR recovery was above or below the median V LA4 and HR recovery values of SET-I [4,10]. …”
Section: Methodsmentioning
confidence: 99%